Shrinking regions in a shrinking country: The geography of population decline in Lithuania 2001-2011 - Ubarevičienė, Rūta; van Ham, Maarten; Burneika, Donatas (A+BE | Architecture and the Built Environment, 2018)
Shrinking populations have been gaining increasing attention, especially in postsocialist East and Central European countries. While most studies focus on specific cities and regions, much less is known about the spatial dimension of population decline on the national level and the local factors determining spatially uneven population change. This study uses Lithuanian census data from the years 2001 and 2011 to get insight into the geography of population change for the whole country. Lithuania has experienced one of the highest rates of population decline in the world in the last decades. The predictive models show that regional factors have a strong effect on the variation in population change throughout the country but also reveal that sociodemographic and economic area characteristics play a role in the process of decline. Our results give little hope to those who would like to reverse the ongoing trends of population change and emphasize the need for spatial planning to cope with the changes. This is an approach which currently does not exist in practice in Lithuania.